Computer Supported Qualitative Research - Costa, António Pedro; Reis, Luís Paulo; Neri de Sousa, Francislê; Moreira, António; Lamas, David; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book contains an edited selection of the papers accepted for presentation and discussion at the first International Symposium on Qualitative Research (ISQR2016), held in Porto, Portugal, July 12th-14th, 2016. The book and the symposium features the four main application fields Education, Health, Social Sciences and Engineering and Technology and seven main subjects: Rationale and Paradigms of Qualitative Research (theoretical studies, critical reflection about epistemological dimensions, ontological and axiological); Systematization of approaches with Qualitative Studies (literature review, integrating results, aggregation studies, meta -analysis, meta- analysis of qualitative meta- synthesis, meta- ethnography); Qualitative and Mixed Methods Research (emphasis in research processes that build on mixed methodologies but with priority to qualitative approaches); Data Analysis Types (content analysis , discourse analysis , thematic analysis , narrative analysis , etc.); Innovative processes of Qualitative Data Analysis (design analysis, articulation and triangulation of different sources of data - images, audio, video); Qualitative Research in Web Context (eResearch, virtual ethnography, interaction analysis , latent corpus on the internet, etc.); Qualitative Analysis with Support of Specific Software (usability studies, user experience, the impact of software on the quality of research.
Research Through Design: Qualitative Analysis to Evaluate the Usability -- Understanding Participatory Policymaking Processes: Discourse Analysis in Psychosociological Action Research -- Combined Use of Software that Supports Research and Qualitative Data Analysis: Potential Applications for Researches in Education -- Use of the Software IRAMUTEQ in Qualitative Research: an Experience Report -- Implementation of Focus Group in Health Research -- The Informal Intercultural Mediator Nurse in Obstetrics Care -- Potentialities of Atlas.ti for Data Analysis in Qualitative Research in Nursing -- Computer Assisted Qualitative Data Analysis Software. Using the NVivo and Atlas.ti in the Research Projects Based on the Methodology of Grounded Theory -- Unpacking the Relationship Between Learning to Read and Mental Health: Using an Ethnographic Case Study Approach -- Reverse Logistics Companies' Perspective: A Qualitative Analysis -- E-mentoring: a Content Analysis Design -- Occupational Therapy's Intervention on Mental Health: Perception of Clients and Occupational Therapists About Intervention Priorities.
Keywords: Computational intelligence; Application software; Computational Intelligence; Computer and Information Systems Applications